Job Access and Homicide Patterns in Chicago: An Analysis at Multiple Geographic Levels Based on Scale-Space Theory - Wang, Fahui (Journal of quantitative criminology, 2005)
Economists and criminologists have long tried to establish linkages between job markets and crime. Most prior research, however, was across large areas (e.g., states, metropolitan areas) or across time. This research focuses on examining the variation of job markets within a city (i.e., Chicago) and whether it is related to the spatial pattern of crime (i.e., homicide). The job market condition is measured by job accessibility, an index computed by a Geographic Information System (GIS) method. Multivariate regressions, controlling for other socioeconomic covariates, are used to analyze the relationship between job access and homicide rates. Considering problems with analysis of rare events such as homicide in small populations, this research constructs various levels of geographic areas from census tracts to generate more stable homicide rates with larger base populations. In particular, a spatial clustering method based on the scale-space theory is used to merge adjacent tracts of similar attributes into new geographic areas. The study shows an inverse relationship between job accessibility and homicide rates across census tracts and the newly-constructed geographic areas in Chicago.